Einstein light to the power of 2 - Soles, Paul.; Studwood, LaTaye; Storey, Raymond; Devine, David, producer ([Toronto] : Devine Entertainment, 2001)
A dramatization of the life and times of Albert Einstein, including the effects of the McCarthy hearings on his life and that of his fellow scientists and his influence on a young black girl and her family in the South.
Originally broadcast as an HBO original programming, The inventors' specials.
Title from disc surface.
Special features include: the life and times of Albert Einstein, music soundtrack, digitally mastered, Dolby digital stereo, production notes, cast and crew credits, access to DEC website, scene access.
Created by David Devine and Richard Mozer ; produced by Richard Mozer ; co-producer Kieran Corrigan.
Paul Soles (as Einstein), LaTaye Studwood, Chris McKinney, Sybyl Walker, Linda Sorensen, Tom Rack, Sandra Caldwell, Shelley Peterson.
Not rated by the MPAA.
Keywords: Einstein, Albert, -- 1879-1955 -- Juvenile films; Video recording for the hearing impaired